Application of Process Quality Control in Leather Industry - K. Logmen, Ayoub; K. Abusabah, Prof. Elnour; Suliman, Dr. Abdalla M. A. (Gezira Journal of Engineering and Applied Sciences; مجلد 9 عدد 2 (2014), 2018)
Quality Control is the regulatory process measuring actual quality performance, comparing it with standards, and rectifying the difference. The objective of this study was to design control charts for raw and export goat skins to ensure that non-defective items are used, and to ensure that defective items are not passed to customers. Ten random samples of raw goat skins of different sizes (32 – 125pieces) were taken and inspected, and then a control chart was drawn. For outgoing wet blue goat skin, ten samples of the same size each of (125pieces) were taken and inspected then a control chart was drawn. The results were as follow; the process involved in delivery of raw skins was out of control, because the proportion defective (0.2080) in one of the samples was located above the upper action limit. The process of outgoing skin showed stability on control chart because all samples were within control limits.